The usefulness of laparoscopic hernia repair in the management of incisional hernia following liver transplantation - Hegab, Bassem (J Minim Access Surg, 2016)
INTRODUCTION: The reported incidence of incisional hernia following orthotopic liver transplantation (OLT) varies from 4% to 23%. Postoperative wound complications are less frequent after laparoscopic repair while maintaining low recurrence rates. We present our experience in managing this complication. MATERIALS AND METHODS: Retrospectively, collected data of all patients who underwent liver transplant and developed incisional hernias were analyzed. Patients’ demographic data, anthropometric data, transplantation-related data, and repair-related operative and postoperative data were collected. Risk factors for post-transplant incisional hernia were appraised in our patients. Patients were divided into two groups: Group A included patients who had their incisional hernia repaired through the laparoscopic approach, and Group B included patients who had their incisional hernia repaired through open conventional approach. RESULTS: A total of 488 liver transplantations were performed at our institution between May 2001 and end of December 2012. Thirty-three patients developed incisional hernias after primary direct closure of the abdominal wall with an overall incidence of 6.9%. Hernia repair was done in 25 patients. Follow-up ranged from 6.4 to 106.1 months with a mean of 48.3 ± 28.3 months. All patients were living at the end of the follow up except four patients (16%). Group A included 13 patients, and Group B included 12 patients. The size of defects and operative time did not differ significantly between both the groups. On the other hand, hospital stay was significantly shorter in laparoscopic group. Complication rate following laparoscopic repair was insignificantly different for open repair. CONCLUSION: In experienced hands, laparoscopic incisional hernia repair in post-liver transplant setting proved to be a safe and feasible alternative to open approach and showed superior outcome expressed in shorter hospital stay, with low recurrence and complication rate.